2022
DOI: 10.3329/bjb.v51i1.58824
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anthropogenic Activities on Physico-Chemical Properties of Sediment of Hokersar Wetland: A Protected Wildlife Reserve (Ramsar Site No.1570) Of Kashmir Himalaya

Abstract: Impact of anthropogenic activities on physico-chemical properties of sediment of Hokersar wetland was carried in summer, spring and autumn seasons. Sediment at Inlet site was having higher value for physicochemical parameters viz; EC (0.509 dS/m), available nitrogen (109.86 mg/kg), available potassium (89.97 mg/kg), available phosphorus (10.18 mg/kg), Ca (352.53 mg/kg) and Mg (152.44 mg/kg) except pH which was highest (7.99) at Outlet. The values of all the physico-chemical parameters of sediment were found ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Singh et al (Wani et al, 2018a;Padder et al, 2022) also reported less spot blotch severity in early sown crop than late sown crop. The per cent seed infection depends on spot blotch disease severity and low disease severity was recorded in early sown crop plot as also reported earlier by (Bhat et al, 2017;Malik et al, 2018;Bano et al, 2022) wherein timely sown crop was less affected by spot blotch than late sown. Data regarding the individual effects of nutritional amendments (Table 1a) clarified that FYM @ 5 t/h lead to the highest values of PDI (76.50%) as well as seed infection (58.38%) followed by RDF with PDI and seed infection values of 74.93 and 50.50%, respectively.…”
Section: Effects On Disease Incidence and Severitysupporting
confidence: 79%
“…Singh et al (Wani et al, 2018a;Padder et al, 2022) also reported less spot blotch severity in early sown crop than late sown crop. The per cent seed infection depends on spot blotch disease severity and low disease severity was recorded in early sown crop plot as also reported earlier by (Bhat et al, 2017;Malik et al, 2018;Bano et al, 2022) wherein timely sown crop was less affected by spot blotch than late sown. Data regarding the individual effects of nutritional amendments (Table 1a) clarified that FYM @ 5 t/h lead to the highest values of PDI (76.50%) as well as seed infection (58.38%) followed by RDF with PDI and seed infection values of 74.93 and 50.50%, respectively.…”
Section: Effects On Disease Incidence and Severitysupporting
confidence: 79%
“…Many scholars have studied the trace element contamination of surface water in different locations in India (Ram and Singh, 2007;Tiwari et al, 2016;Lohani et al, 2008). Trace element pollution has been assessed by the distribution of particle size and the organic content present in the water system (Saif and Khan, 2017;Bano et al, 2018;Prieto et al, 2018). The bioavailability of trace elements depends on the concentration of anions, chelating agents in the water, pH, and the presence of absorptive sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The unplanned and unregulated development of urbanisation during the last two decades has resulted in the degradation of environmental health, particularly in developing countries like India (Rauf et al, 2009;Madhav et al, 2020;Bano et al, 2022). A number of anthropogenic activities may alter the dynamic properties of lotic ecosystems by adding heavy metals to the water bodies (Cortecci et al, 2009;Bhat et al, 2011;Hasan et al, 2021;Khan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(World Health Organization, 2008). Anthropogenic activities are degrading the world's water resources, reducing their accessibility for domestic, drinking, irrigation, shing, outdoor enjoyment, and industrial purposes (Shit, Bano et al 2022). Concerns have also been raised about the urban streams that run through these neighbourhoods being used as dumping grounds by both homes and businesses (Bhat et al, 2011;Phiri et al, 2005;Enguito et al, 2013;Sharma et al, 2020;Mihai et al, 2020;Datta et al, 2022).…”
Section: Introductionmentioning
confidence: 99%